Planning the (dis)connected city: Why gated projects get approved - Grant, Jill (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 2005)
AbstractA strong consensus around values of mixed use, connected streets, and alternative transportation modes drives urban planning theory in most Western nations today. Smart growth and sustainable development models promote diversity, affordability, and connectedness in a vibrant public realm. At the same time, though, we note that gated developments are on the increase. How can we account for the proliferation of homogeneous, isolated, and car-oriented enclaves when those who regulate land use advocate quite different options? This article identifies the principles that planners agree on and uses a case study of Canadian planning practice to illustrate why gated projects get approved regardless of planners’ preferences. In an environment where affluent consumers prefer homogeneity and exclusivity, and where local government is looking for cost-effective options when investing in new urban infrastructure, decision makers may feel compelled to accept gated enclaves as a viable development option.